Understanding middle leaders' concerns in curriculum change: a missing perspective. Issue 4 (2nd October 2021) - Loh, Jason; Hu, Guangwei
ABSTRACT: This paper is a case study evaluating the concerns that middle leaders in Singapore schools had as they implemented a large-scale English language curriculum reform. Drawing on in-depth interviews, the study aimed to gain insights into middle leaders' perspectives. Its findings indicated that middle leadership could exert a substantial influence on educational change within a school. Not only were they able to influence their teachers' understanding, but they also held some sway over the teachers' receptivity towards and enactment of the reform. In addition, there were commonalities among the middle leaders' concerns about the curriculum reform. As reform policies tend to differ from school priorities, failure to address middle leaders' concerns has wide implications for curriculum reform and implementation.